The frequency of infection with high-risk human papilloma virus types on the cervix uteri of women of reproductive age - Prelić, Jovana; Knežević, Aleksandra (Medicinski podmladak, 2022)
Introduction: Human papillomavirus is the most important etiological factor that leads to the malignant alteration of cervical epithelium. More than 200 types of human papillomavirus are identified. Based on its oncogenic potential, human papillomavirus can be classified as low-oncogenic and high-oncogenic types. Aim: To determine the frequency of infection with high-risk human papillomaviruses in the cervical swabs of reproductively active women in our population. Materials and methods: The research is designed as descriptive study. Data on the presence of HPV infections as well as the virus genotype in 707 cervical swab from the period from January 2019 to August 2020, as well as the correlation with the woman’s age and cytological status on the cervix, were analyzed. Results: HPV infection was present in 223 out of 707 tested samples (31.54%). The highest frequency of HPV infection, as well as the highest number of HPV genotypes was in the group of women aged 25-34 years (36.32%). The frequency of HPV infection correlates with altered cytological status. The presence of 26 HPV genotypes was determined, 16 highly oncogenic and 10 low oncogenic types, of which the most common was highly oncogenic type 16 (25.11%). Conclusion: These findings showed a high frequency of highly oncogenic HPV genotypes, primarily type 16 in most groups of women of reproductive age. In addition, the frequency of infection correlates with cytological status, which indicates the great importance of prevention of genital HPV infection in our female population. Keywords: HPV, carcinoma, genotyping